Optimalisasi Produksi pada UMKM Industri Tahu dengan Linear Programming - Anugerah, Adhe Rizky; Kharismawati, Anisa; Wijayanti, Nanik; Falaq, Iqbal Abdul; Kamil, Rafi Adlan; Sari, Saprina Melita (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
MSMEs (Micro, Small, and Medium Enterprises) are crucial to Indonesia's economy. However, limited resources and suboptimal management remain key challenges for business sustainability. This study aims to optimize tofu production in Yogyakarta’s MSMEs using the linear programming method, specifically the simplex method. The research focuses on three constraints: soybeans, salt, and working hours, with the goal of maximizing profit through an efficient combination of white tofu and Magel tofu production. Data was collected through field interviews and analyzed using the simplex method with POM/QM. The results show that the business needs to produce 14 buckets of white tofu ( 1,400 pcs) and 6 buckets of Magel tofu ( 600 pcs) to achieve maximum revenue of IDR 2,176,146. Sensitivity analysis on increasing Magel tofu prices did not affect the optimal solution within the tolerance range. This research offers empirical insights for MSME decision-making and theoretical contributions to linear programming applications in creative industry.